Cream skimming in the insurance market and mechanisms that exist to reduce its effect / Rosmi Yuhasni Mohamed Yusuf - Mohamed Yusuf, Rosmi Yuhasni (2003)
Attempts to attract low risk clients or equivalently to discourage those with high risk from signing up an insurance policy are often referred to in the literature as cream skimming or cherry picking. This paper intends to explain the extent of cream skimming as a practice that could lead to the overall inefficiency in the insurance market, with particular attention given to the private insurance market. The first part of this paper will discuss around the basic theory of insurance market with asymmetric information with reference to the seminal work of Rothschild and Stiglitz (1976) that should be used to theoretically explain the basic reason of cream skimming practices among the insurers. The second part of this paper will discuss on the mechanisms available to reduce the magnitude of cream skimming problem such as regulation, risk adjustment and risk sharing with specific reference to the provision of individual health insurance in countries such as the Netherlands and the United States as widely discussed in the academic literature.